The Julio-Claudian Roman Family and Their Role in Establishing the Foundations of the Early Imperial Age (14–68 AD) - Obeid, Ass. Lecturer Mohammed Aziz (Thi Qar Arts Journal, 2024)
The Julio-Claudian family was credited with solidifying the foundations of the Roman Empire, which was anxious due to the deeply rooted republican thought in the Senate (Senatus), which was looking for opportunities to pounce on the empire and return it to the republican era. However, this family stood against this project by creating the Imperial Guard (Praetorian), especially after the assassination of Julius Caesar inside the Senate with knives by the council members. The decisive word in the power transition process was for the leaders of the Imperial Guard, whose command to maintain their influence and dominance was linked to the emperor’s survival; therefore, they stood against the return of the republic.